Abbreviated resonant frequency training to augment heart rate variability and enhance on-demand emotional regulation in elite sport support staff - Gross, M. J.; Shearer, D. A.; Bringer, J. D.; Hall, R.; Cook, C. J.; Kilduff, L. P. (Applied Psychophysiology and Biofeedback, 2016)
Support and management staff in elite sport experience work-related stress and emotional disturbance to a similar extent as athletes (Fletcher and Wagstaff 2009). The resonant frequency breathing technique (Lehrer et al. 2000) can inhibit autonomic changes associated with stressful situations or events and as such provides a potential emotional regulation tool. The present study utilised five practitioner-led heart rate variability (HRV) biofeedback sessions and home practice via mobile applications to train support and management staff (n = 9) in resonant frequency breathing techniques. Although baseline HRV did not change from pre to post training, participants increased total HRV (i.e., SDNN; p = .006), parasympathetic HRV (i.e., RMSSD; p = .028) and HRV reflective of baroreflex function (i.e., low frequency power; p = .018) while accurately performing resonant frequency breathing without a breath pacer. Post-intervention questionnaire data revealed an increase (p = .032) in habitual use of somatic strategies for emotional regulation, and social validation data suggested that the technique enhanced emotional regulation at home, work and during international competition. HRV biofeedback and the resonant frequency technique provided an on-demand emotional regulation technique for elite sport support and management staff.